Inside the Equal Access to Justice Act: Environmental Litigation and the Crippling Battle over America's Lands, Endangered Species, and Critical Habitats - Baier, Lowell E. (Rowman & Littlefield Publishers, 2015)
Next Generation INDIE Book Awards Grand Prize Winner, Best Non-Fiction Book in 2017; and Winner in the Science/Nature/Environment category Finalist for Foreword INDIES Book of the Year Awards in Ecology and Environment In this book, Lowell E. Baier, one of America’s preeminent experts on environmental litigation, chronicles the century-long story of Americas’ resources management, focusing on litigations, citizen suit provisions, and attorneys’ fees. He provides the first book-length comprehensive examination of the little-known Equal Access to Justice Act (EAJA) and its role in environmental litigation. Originally intended to support veterans, the disabled and small business, EAJA, Baier argues, now paralyzes America’s public land management agencies. Baier introduces readers to the history of EAJA, examines the many beneficiaries of the law, describes in depth 20 of the most prominent litigious environmental groups in America, and recommends carefully tailored amendments to the EAJA to correct environmental abuses of the law while protecting legitimate interests. Inside the Equal Access to Justice Act will be a valuable resource for the environmental legal community, environmentalists, practitioners at all levels of government, and all readers interested in environmental policy and the rise of the administrative state.